2021
DOI: 10.15252/embr.202152785
|View full text |Cite
|
Sign up to set email alerts
|

An EZH2‐dependent transcriptional complex promotes aberrant epithelial remodelling after injury

Abstract: Unveiling the molecular mechanisms of tissue remodelling following injury is imperative to elucidate its regenerative capacity and aberrant repair in disease. Using different omics approaches, we identified enhancer of zester homolog 2 (EZH2) as a key regulator of fibrosis in injured lung epithelium. Epithelial injury drives an enrichment of nuclear transforming growth factor‐β‐activated kinase 1 (TAK1) that mediates EZH2 phosphorylation to facilitate its liberation from polycomb repressive complex 2 (PRC2). T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…In this context, AAV’s low immunogenicity in mice is an important property, as it allows for specific modulation of pathways without interference by vector-targeted immune responses. Since its development, the AAV-TGFβ1 model has been frequently used to study drug candidates and explore target function in our group 68 70 . Further technological refinement of the model might be achieved in the future by using self-complementary AAV vectors, which lead to a faster onset of transgene expression 71 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, AAV’s low immunogenicity in mice is an important property, as it allows for specific modulation of pathways without interference by vector-targeted immune responses. Since its development, the AAV-TGFβ1 model has been frequently used to study drug candidates and explore target function in our group 68 70 . Further technological refinement of the model might be achieved in the future by using self-complementary AAV vectors, which lead to a faster onset of transgene expression 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that Ezh2 null organoids have a significant loss in a Krt5 − /Krt17 + /Krt8 + /Fn1 + cell population suggests that Ezh2 expression may be a key contributor to the pathology of pulmonary fibrosis. A recent paper showed that inhibition of EZH2 by the inhibitor, GSK126, was able to abrogate transforming growth factor β-induced lung fibrosis phenotypes, and our organoid model presents additional mechanistic insight into this phenomenon ( Le et al., 2021 ). The increased expression of AT2 marker Lamp3 and the alveolar developmental marker Foxp2 suggests that loss of Ezh2 expression leads to accumulation of BASC/AT2 progenitor cells that may be unable to transition into the KRT8 + state, or further into AT1 cells.…”
Section: Discussionmentioning
confidence: 71%
“…It plays an essential role in both IPF and GERD. The POLR2 plays a crucial role in the abnormal repair of respiratory epithelial cells ( Le et al, 2021 ). It also develops esophageal acidic microenvironment pH by binding to eotaxin-3 protein, an essential target of eosinophilic esophagitis ( Zhang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%